Effect of chemical modifications of tannins on their antimicrobial and antibiofilm effect against Gram-negative and Gram-positive bacteria - Villanueva, Xabier; Zhen, Lili; Ares, José Nunez; Vackier, Thijs; Lange, Heiko; Crestini, Claudia; Steenackers, Hans P. (Frontiers in Microbiology, 2023)
(1) Background: Tannins have demonstrated antibacterial and antibiofilm activity, but the mechanisms of action are not completely elucidated. We are interested in understanding how to modulate the antibiofilm activity of tannins and in delineating the relationship between chemical determinants and antibiofilm activity. (2) Materials and methods: the effect of five different naturally acquired tannins and their chemical derivatives on biofilm formation and planktonic growth of Salmonella Typhimurium, Pseudomonas aeruginosa, Escherichia coli and Staphylococcus aureus was determined in the Calgary biofilm device. (3) Results: most of the unmodified tannins exhibited specific antibiofilm activity against the assayed bacteria. The chemical modifications were found to alter the antibiofilm activity level and spectrum of the tannins, with a positive charge introduced by derivatization with higher amounts of ammonium groups shifting the anti-biofilm spectrum towards Gram-negative bacteria, and derivatization with lower amounts of ammonium groups and acidifying derivatization shifting the spectrum towards Gram-positive bacteria. Furthermore, the quantity of phenolic OH-groups per molecule was found to have a weak impact on the anti-biofilm activity of the tannins. (4) Conclusions: we were able to modulate the antibiofilm activity of several tannins by specific chemical modifications, providing a first approach for fine tuning of their activity and antibacterial spectrum.